INTEGRASI CHARACTER VALUE MELALUI PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR - Hasni Noor (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2022)
This study aims to determine the integration of character values in learning Islamic Religious Education at SDN Tinggiran Darat. Descriptive qualitative method was applied in this study, while the data were obtained through interviews, observation and documentation. After the data was collected, the researchers analyzed the data from the Miles and Huberman model. The validity of the data has been checked by triangulation in an effort to ensure the data that has been obtained is valid and correct. The results of this study describe PAI teachers at SDN Tinggiran Darat have integrated character values into Islamic Religious Education subjects. Integration is applied in learning planning and in the learning process. In planning the teacher inserts character values starting from the initial activity to the final activity, while in the learning process character values are directly integrated into learning activities. The PAI teacher also evaluates the PAI material and at the same time on the student's character which is carried out through observation, self-assessment and peer-assessment.